Controle social e políticas públicas: contribuições para aprimorar o controle social do programa nacional de alimentação escolar - Paludo, André Carlos (2015)
The National School Feeding Programme (PNAE) is a public policy in Brazil for over 60 years and represents one of the most important programs of feeding and nutrition in the world. The role of family farming as a source of employment in rural areas, food provider and for ensuring much of the Brazil’s food security is constantly present at the government's and social movement’s agendas. Law 11.947 of 2009 marked its integration in the food supply for the National School Feeding Programme. Article 14 of aforementioned law highlights that a minimum of 30% (thirty percent) of the funds transferred by the National Development Fund Education (FNDE) to the Programme must be used for the purchase of food directly from family farmers or their organizations. The national school feeding policy under the responsibility of the FNDE and is subjected to agencies of internal control, such as the General Controllership of the Union (CGU), of external control, such as the Audit Courts of the Union and the of the states, and to the social control of the school feeding councils. Those funds are transferred to the implementing agencies, which are the education offices of the states, municipalities and of the Federal District. These entities must annually present their accountings to the School Feeding Councils, which analyze them and then issue a conclusive report to the FNDE, approving with or without reservations, or rejecting them. In this sense, this research aims to propose parameters that should contribute to the improvement of the social control over purchases from family farming for the National School Feeding Programme. The study was conducted by non parametric sampling alongside the managers of the implementing entities, school feeding councils and Family Farming Organizations all across Brazil, from the databases provided by FNDE and by the National Union of Cooperatives of Family Agriculture and Solidarity Economy (Unicafes). The study points out that the legal framework of PNAE seeks to ensure the participation of family farming in the food supply for the Programme, despite allowing the executing agencies to justify the non-compliance of the minimum required in a number of ways. The survey also signalizes that the school feeding councils follow the implementation of the Programme very shyly, and points out that there is room to expand and enhance the participation of these councils and organizations of family farming in the execution of PNAE. Its effectiveness requires a constant and effective process of training of the agents involved in the Programme.